3c+6-4c=4+2c

Simple and best practice solution for 3c+6-4c=4+2c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3c+6-4c=4+2c equation:


Simplifying
3c + 6 + -4c = 4 + 2c

Reorder the terms:
6 + 3c + -4c = 4 + 2c

Combine like terms: 3c + -4c = -1c
6 + -1c = 4 + 2c

Solving
6 + -1c = 4 + 2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-2c' to each side of the equation.
6 + -1c + -2c = 4 + 2c + -2c

Combine like terms: -1c + -2c = -3c
6 + -3c = 4 + 2c + -2c

Combine like terms: 2c + -2c = 0
6 + -3c = 4 + 0
6 + -3c = 4

Add '-6' to each side of the equation.
6 + -6 + -3c = 4 + -6

Combine like terms: 6 + -6 = 0
0 + -3c = 4 + -6
-3c = 4 + -6

Combine like terms: 4 + -6 = -2
-3c = -2

Divide each side by '-3'.
c = 0.6666666667

Simplifying
c = 0.6666666667

See similar equations:

| 9/10x=9 | | -16t^2+88t-40=0 | | 112.07=4s+17.03 | | 4x+25=x | | 3c+6-4c=4+2x | | 15w^2-14w+3=0 | | 3(2k-7)-4=-(2k-7) | | -13=-r-6 | | (4b-3)(5b+6)= | | 51-9-6=v | | k+10=-3 | | HX=WQx | | P=5L-4W | | (4-i)-(7+2i)= | | x^4-16x^3=y^3 | | 4m-12=91+5m | | y-(-1)=-5 | | -4n+5=1-3n | | h=-16t^2+88t | | 3/4x-2=1 | | 6x+158=8x+188 | | 19=2x+11 | | -22d-3d=2d+d-3d | | 9/8X3/5 | | 1/2x13=9 | | 1+2n+3n=9+4n | | 6x+7=4x+2x | | 2w-4=8 | | 6-10n=36 | | -6i*6i= | | 6C-7=0 | | 2x(4x-5)=20 |

Equations solver categories